Pengaruh Lama Perendaman Buah dan Fermentasi terhadap Warna Kulit Tanduk dan Citarasa Kopi Robusta - Khalimatus Sa'diyah; Usman Ahmad; Sukrisno Widyotomo; Yusianto Yusianto (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Pulping and fermentation of coffee cherry determine the quality of green beans and coffee flavors. Delay in pulping will cause the slime stick to the hull skin hence decreasing the bean quality and flavor. The objective of this study was to examine the effect of soaking before pulping and fermentation time to the color of coffee hull skin and the cup quality. The research was carried out at the experimental station of Indonesian Coffee and Cocoa Research Institute in Malang Regency (ICCRI) and ICCRI laboratory in Jember Regency from July 2018 to January 2019. Experiments used factorial completely randomized design. The first factor was cherry soaking duration (0, 24, 48, and 72 hours) and the second factor was fermentation duration (0, 24, and 48 hours) and then combined into 12 treatments, with three replications. Ten kilograms of coffee cherries were soaked prior to pulping then fermented in a plastic bag and added with Lactobacillus casei 2,5 x 107 cfu/ml as starter. Parameters observed were color of hull skin (L value, a*, dan b*) and the cup quality. The results showed that soaking the cherry decreased the green beans quality which is indicated by less brightness (L), high a* value, and decreasing b* value of hull skin color. While the fermentation treatment can increase the value of L, decrease the a* value, and increase the b* value. The interaction of treatment of soaking and fermentation time significantly affected the lightnessl a* and b* value. Soaking and fermentation treatments did not significantly affect to the flavor, salt/acid, balance, and total score of coffee flavor. Soaking is not recommended for more than 48 hours and fermentation should be carried out 48 hours.